Xylo-oligosaccharides display a prebiotic activity when used to supplement wheat or corn-based diets for broilers - Ribeiro, T. (2018)
It is now well established that exogenous β-1,4-xylanases improve the nutritive value of wheat-based diets for poultry. Among other factors, the mechanism of action of exogenous enzymes may involve a microbial route resulting from the generation of prebiotic xylo-oligosaccharides (XOS) in the birds' gastro-intestinal (GI) tract. In a series of three experiments, the effect of XOS on the performance of broilers fed wheat or corn-based diets was investigated. In experiment 1, birds receiving diets supplemented with XOS displayed an increased weight gain (P = 0.08). The capacity of XOS to improve the performance of animals during a longer trial (42 d) was investigated (Experiment 2). The data revealed that diet supplementation with XOS, tested at two incorporation rates (0.1 and 1 g/kg), or with an exogenous β-1,4-xylanase resulted in an increased nutritive value of the wheat-based diet. An improvement in animal performance was accompanied by a shift in the microbial populations colonizing the upper portions of the GI tract. XOS were also able to improve the performance of broilers fed a corn-based diet, although the effects were not apparent at incorporation rates of 10 g/kg. Together these studies suggest that in some cases the capacity of β-1,4-xylanases to improve the nutritive value of wheat-based diets is more related to their ability to produce prebiotic XOS than to their ability to degrade arabinoxylans. The extremely low quantities of XOS used in this study also challenge the depiction of a prebiotic being a quantitatively fermented substrate. These data also bring into question the validity of the "cell wall" mechanism, as XOS elicited an effect with clearly no action on endosperm cell wall integrity and yet the performance effects noted were equivalent or superior to the added enzymes.